THE METAPHOR OF MODALITY IN THE BOOK CONVERSATIONS ON LOVE BY NATASHA LUNN: Metafora Modalitas dalam Buku Conversations on Love karya Natasha Lunn - Nabillah, Bilqis; Garnida, Susie Chrismalia (TANDA, 2025)
The metaphor of modality is a language variation in the expression of modality. Analyzing the metaphor of modality is essential to see the validity of the speaker’s statement in interpersonal communication. The theory of the metaphor of modality by Halliday and Matthiessen (2014) was applied to see the use of the metaphor of modality in the self-development book. This study aimed to find the types and values of the metaphor of modality used by speakers during conversations in the book. The method of this study was descriptive qualitative. This study found 53 data containing the metaphor of modality in the book Conversations on Love by Natasha Lunn. The data were categorized into types and values of probability, obligation, and inclination. The type of probability has 40 data, the type of obligation has 6 data, and the last type of inclination has 7 data. Then, the value of metaphor of modality was found with a median value of 28 data, a high value of 23 data, and a low value of 2 data.